2021
DOI: 10.15294/jhe.v6i1.42898
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Knowledge and Attitudes on Tuberculosis Patients with Poster Calendar and Leaflet

Abstract: Background: Leaflet and poster calendars are one medium to provide health education to patients with pulmonary tuberculosis on the treatment of pulmonary Tuberculosis. The purpose of this research for media want to effectivity leaflet and poster calendars on health promotion to improve the knowledge and attitudes of pulmonary tuberculosis treatment at the Martubung Public Health Center. Methods: Research is a quasi-experimental design with pre-test and post-test group. The population in this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…48 Another study found that poster calendar interventions and leaflet media could be used to improve pulmonary TB patients' knowledges and attitudes at the Martubung Health Center. 49 The Mann-Whitney test results showed that health education using video and leaflet had a significant effect on TB patients by increasing knowledges (p=<0.001), attitudes (p=<0.001), and practices (p=<0.001). These findings also indicated that there was a significant increase in the mean knowledges, attitudes, and practices score of the intervention group compared to the controls.…”
Section: Resultsmentioning
confidence: 96%
“…48 Another study found that poster calendar interventions and leaflet media could be used to improve pulmonary TB patients' knowledges and attitudes at the Martubung Health Center. 49 The Mann-Whitney test results showed that health education using video and leaflet had a significant effect on TB patients by increasing knowledges (p=<0.001), attitudes (p=<0.001), and practices (p=<0.001). These findings also indicated that there was a significant increase in the mean knowledges, attitudes, and practices score of the intervention group compared to the controls.…”
Section: Resultsmentioning
confidence: 96%
“…Age, where the older a person is, the better his mental development process, intelligence, or ability to learn and think to adapt to new situations, then the environment where a person can learn good and bad things depending on the nature of the group, a culture that plays an important role in knowledge, and education is fundamental to developing knowledge and experience and is also the best teacher in developing nutrition knowledge (Siregar, 2021); (Hanum, 2020).…”
Section: Discussmentioning
confidence: 99%
“…Metode intervensi yang diterapkan pada penelitian ini dengan melibatkan masyarakat sebagai responden menunjukkan pengaruh yang positif pada pengetahuan dan sikap terhadap pencegahan tuberculosis (Siregar, 2021;Andarmoyo, 2019; Cahyaningtyas dan Harlianti, 2019). Meskipun terdapat beberapa penelitian yang menganalisis pengetahuan dan sikap terhadap pencegahan tuberkulosis, akan tetapi tidak satupun dalam peneitian tersebut yang melibatkan masyarakat sebagai subjek penelitian.…”
Section: Pembahasanunclassified